Effect of vermicomposting plant residues on phytochemical properties of Zarrin-giah (Dracocephalum kotschyi Boiss.) - Maedeh Bohlouli; Hossein Ali Asadi-Gharneh; Elham Chavoshi; Nafiseh Zamindar (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: This study was conducted to evaluate whether vermicompost production from various plant residuals could improve the biomass and essential oil properties of Zarrin-giah (Dracocephalum kotschyi Boiss.).